Otimização de marcadores químicos para a avaliação da atividade antinociceptiva e influência de fatores abióticos nas concentrações de flavonas c-glicosiladas presentes nas folhas de Echinodorus macrophyllus (KUNTH) Micheli - Strada, Claudia Léia (2012)
Echinodorus macrophyllus (Kunth) Micheli (Alismataceae) is a perennial herb which is found only in flooded areas in South America. In popular medicine, the leaves are used under the decoction or infusion form primarily as a diuretic and anti-inflammatory. Chemical Studies done with these species has shown the presence of diterpenes and C-glycosides flavonoids as major constituents. Based on the premise that the anti-inflammatory activity observed can be at least in part, assigned flavonoids, the objective of this work was identify and quantify the vitexin (37), vitexin-2-Orhamnoside (41) e isovitexin (5) flavonoids in hydroethanolic extracts on the leaves E. macrophyllus and E. grandiflorus (EhEm) coleted on 11 distints areas in MT and MS, correlating their concentrations with their environmental variables and antinociceptive activity, into models of abdominal contortions induced on Swiss Mice. The identification and quantitation were performed by CLAE-DAD. The results show that (37) was detected only in trace amounts in an extract. The concentration of (41) ranged from 5.430 to 33.130 μg.mg-1 was not detected in two extratos ea (5) was the only flavonoid present in all samples and detected in trace amounts in extracts from two locations and quantified in too, with concentrations ranging from 0.620 to 14.700 range μg.mg-1. Studies of the analgesic activity of the extracts showed that all eleven significantly inhibited the pain, and the percentage of inhibition varied from 47% to 79% at both doses tested, whereas with indomethacin (5 mg.kg-1) the percentage inhibition ranged from 82% to 90%. Not was observed no correlation between concentrations of flavonoids (41) and (37) and antinociceptive activity. However, there is an increasing trend between the concentration of (5) and activity mentioned. Therefore, it seems reasonable to propose that isovitexin (5) can be used as chemical marker when trying to correlate with antinociceptive EhEm prepared from specimens collected at various locations.